9x+6(100)=7x+700

Simple and best practice solution for 9x+6(100)=7x+700 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+6(100)=7x+700 equation:


Simplifying
9x + 6(100) = 7x + 700

Multiply 6 * 100
9x + 600 = 7x + 700

Reorder the terms:
600 + 9x = 7x + 700

Reorder the terms:
600 + 9x = 700 + 7x

Solving
600 + 9x = 700 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
600 + 9x + -7x = 700 + 7x + -7x

Combine like terms: 9x + -7x = 2x
600 + 2x = 700 + 7x + -7x

Combine like terms: 7x + -7x = 0
600 + 2x = 700 + 0
600 + 2x = 700

Add '-600' to each side of the equation.
600 + -600 + 2x = 700 + -600

Combine like terms: 600 + -600 = 0
0 + 2x = 700 + -600
2x = 700 + -600

Combine like terms: 700 + -600 = 100
2x = 100

Divide each side by '2'.
x = 50

Simplifying
x = 50

See similar equations:

| (q+33)+6q=180 | | M+-5=-10 | | z+12=5z | | 92=x(x+4) | | a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 | | (4x+7)+(2x-1)=180 | | K-7=-9 | | 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 | | 2x(x-6)(3x+2)=0 | | 5a^2+3a-2=0 | | -2.3-3x-4.1-x=-3x-0.9 | | ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 | | -2+n=6n+22 | | -3=-15-3x | | 5a-3=a+45 |

Equations solver categories